Exploring the relationship between cathepsin and age-related macular degeneration using Mendelian randomization - Wang, Qiuyuan; Cai, Shanjun (Frontiers in Medicine, 2024)
Purpose Age-related macular degeneration (AMD) is the leading cause of low vision and even blindness in the elderly population worldwide. However, no studies have been conducted to analyze the causal relationship between the cathepsin family and AMD. The present study aimed to explore and analyze this potential association using Mendelian randomization (MR). Methods In this study, AMD was classified into two types: exudative AMD and atrophic AMD. Inverse-variance weighting (IVW) was used as the main analysis method. The association between nine cathepsins and the two classifications of AMD were analyzed using multivariable Mendelian randomization (MVMR). Sensitivity analysis included Cochran’s Q-test and the MR-Egger intercept test. Results Two-sample MR analysis showed that higher levels of cathepsin L2 were associated with a delay in the development of atrophic AMD (IVW: p = 0.017; OR = 0.885; 95% CI = 0.799–0.979). Reverse MR analysis indicated that cathepsin E levels were increased in individuals with atrophic (IVW: p = 0.023; OR = 1.058; 95% CI = 1.007–1.111) and exudative AMD (IVW: p = 0.018; OR = 1.061; 95% CI 1 = 1.010–1.115). MVMR analysis indicated a causal relationship between cathepsin G (IVW: p = 0.025; OR = 1.124; 95% CI = 1.014–1.245), cathepsin O (IVW: p = 0.043, OR = 1.158, 95% CI = 1.004–1.336), and exudative AMD after coordinating for other types of cathepsin. Conclusion This study demonstrated a potential link between the cathepsin family and the onset of AMD. Elevated serum concentrations of cathepsin L2 may serve as a protective factor for atrophic AMD, while increased levels of serum cathepsin G and O concentrations may promote the development of exudative AMD. Besides, the development of AMD may be associated with elevated serum concentrations of cathepsin E.